Efektifitas Kepemimpinan Kepala Madrasah terhadap Mutu Pendidikan MTsN 2 Mojokerto - Achmad Krisbiyanto (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2019)
The head of the madrasa is a leader who has a big responsibility to be able to improve the quality of education in an educational institution. The quality of the institution's education will be able to improve if the head of the madrasa is able to carry out tasks and work properly in accordance with the principal functions of leadership. The leadership function that must be possessed by the head of the madrasa includes Idealism, intellectual, caring and charisma. Improving the quality of education is one of the efforts that can be made to develop human resources for national development. Quality education institutions can be seen from three things, namely input (resources owned), process and output (graduates). Therefore from formal education in schools it is expected that students can develop optimally all the potential that exists in them. So that the school will be able to print graduates who have competency and have high competitiveness.